2021
DOI: 10.1039/d0cp06549h
|View full text |Cite
|
Sign up to set email alerts
|

Twistable dipolar aryl rings as electric field actuated conformational molecular switches

Abstract: The electric field induced conformational response of a range of twistable dipolar aryl ring systems is studied using density functional theory based calculations. We assess which factors are most important for efficient molecular switching.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 55 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…The effects of external electric fields (EEFs) on reactivity have been intensively investigated by computational means in recent years. Calculations based on a rigorous inclusion of the effect of a given electric field on the electrons and nuclei have predicted that EEFs can catalyze many types of reactions (e.g., Diels–Alder reactions, ,, other types of cycloaddition reactions, the Menshutkin reaction, ring opening reactions, electrophilic aromatic substitution reactions, oxidative addition reactions between palladium catalysts and alkyl/aryl electrophiles, the Kemp elimination reaction, thermal isomerization and photoisomerization of azobenzene, degradation of bromobenzene), improve the efficiency of heterogeneous catalysts, , control the selectivity of reactions, ,, cause drastic changes in reaction mechanisms , and induce conformational rearrangements . All these effects can be understood on the basis of the ionicity induced by EEFs on bonds and transition states, which, in turn, can be rationalized using a valence bond perspective. The effect of OEEFs on reactivity can also be rationalized by using quantitative activation strain and Kohn–Sham molecular orbital theory, as recently shown by Bickelhaupt and co-workers .…”
Section: Introductionmentioning
confidence: 99%
“…The effects of external electric fields (EEFs) on reactivity have been intensively investigated by computational means in recent years. Calculations based on a rigorous inclusion of the effect of a given electric field on the electrons and nuclei have predicted that EEFs can catalyze many types of reactions (e.g., Diels–Alder reactions, ,, other types of cycloaddition reactions, the Menshutkin reaction, ring opening reactions, electrophilic aromatic substitution reactions, oxidative addition reactions between palladium catalysts and alkyl/aryl electrophiles, the Kemp elimination reaction, thermal isomerization and photoisomerization of azobenzene, degradation of bromobenzene), improve the efficiency of heterogeneous catalysts, , control the selectivity of reactions, ,, cause drastic changes in reaction mechanisms , and induce conformational rearrangements . All these effects can be understood on the basis of the ionicity induced by EEFs on bonds and transition states, which, in turn, can be rationalized using a valence bond perspective. The effect of OEEFs on reactivity can also be rationalized by using quantitative activation strain and Kohn–Sham molecular orbital theory, as recently shown by Bickelhaupt and co-workers .…”
Section: Introductionmentioning
confidence: 99%
“…Finally, if the orientation of the rings can be manipulated in situ , a spin device can, in principle be constructed to flip between singlet/triplet states by just altering the orientation of the terminal ligand, for instance, by means of an electrical field as in the case of a prototypical biphenyl-based molecular system. 41…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, subsequent STM‐BJ experiments have shown that OEEFs can accelerate other reactions, [41–47] and alternative experimental techniques with greater potential for scalability in utilizing OEEFs have been reported [48–54] . Concurrently with experimental endeavours, significant attention has been devoted to predicting and understanding the effects of OEEFs in reactivity by means of computational studies [55–76] . Remarkably, some of the pioneering computational works were reported much prior to the first experimental evidence of the impact of OEEFs in reactivity [77–81] .…”
Section: Introductionmentioning
confidence: 99%